Comparative characterization of Macaranga species collected from secondary forests in East Kalimantan for biorefinery of unutilized fast growing wood - RUDIANTO AMIRTA; SYAFFIYA ISNU NAFITRI; RETNO WULANDARI; YULIANSYAH YULIANSYAH; WIWIN SUWINARTI; KRISHNA PURNAWAN CANDRA; TAKASHI WATANABE (Biodiversitas Journal of Biological Diversity, 2016)
Amirta R, Nafitri SI, Wulandari R, Yuliansyah, Suwinarti W, Candra KP, Watanabe T. 2016. Comparative characterization of Macaranga species collected from secondary forests in East Kalimantan for biorefinery of unutilized fast growing wood. Biodiversitas 17: 116-123. Wood species for industrial forest plantation has been selected to produce construction wood materials, boards and papers,and unutilized fast growing wood as a source for biofuel production has been out of the scope for selection. Macaranga Thouars (Euphorbiaceae) is widely distributed in the tropics and importance of the genus has been recognized due to its high level of growth rateand adaptability to constitute forest ecosystem. However, potency of the genus as a source for bioethanol production has not beensystematically studied. We herein first report differential properties of six Macaranga wood species collected in East Kalimantan,Indonesia, as a raw feedstock for enzymatic saccharification for bioethanol production. Among the wood species examined, the highestsugar yield 48.6% (weight of original wood basis), which corresponds to 315 mL ethanol/kg biomass, was obtained with 5.0% NaOH at 160ºC for M. hypoleuca. Significant differences in the sensitivity to alkaline concentration and temperature have been found among the species. A high sugar yield, 40.4% was obtained for M. winkleri with a low alkaline concentration, 3.5% NaOH at 150ºC, while M. motleyana gave the sugar yield 12.8% under the same condition. M. motleyana required a set of the conditions with higher NaOH concentration 5.0% and temperatures over 160ºC. The harsh condition with 5.0% NaOH at 170ºC promoted delignification of all the species but M. hypoleuca decreased the saccharification yield by raising the temperature from 160ºC to 170ºC, probably due to decomposition of carbohydrate cores. This temperature-dependent negative effect was not observed with 3.5% NaOH for M. hypoleuca. These results indicate that differences in the balance between disintegration effects and excess degradation of carbohydrates are different among the species and the variation should be taken into account on screening. Thus, we found a wide range of diversity in the susceptibility to alkaline pretreatment in the genus Macaranga and selected the wood species giving high productivity of fermentable sugars.